THE ROLE OF THE UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) IN ETHIOPIAN REFUGEES DURING THE ETHIOPIA-TIGRAY CONFLICT FROM 2018 TO 2021 - Firdaus, Aos Yuli; Widiastuti , Dinda (Journal of Social Political Sciences, 2023)
As one of the international organizations, UNHCR has a role in helping global society in humanitarian areas, especially refugees worldwide. Internally displaced people (IDPs) in Ethiopia become one of the targets for humanitarian access that are affected by the conflict between the Ethiopia federal government ruled by Abiy Ahmed as Primes Minister the Tigray regional that was dominated by Tigray's People Liberation Front (TPLF). The situation in the Ethiopian government changed after the transition of Abiy Ahmed. And then the conflict began after it was triggered by the TPLF when Tigray held its regional general election after Abiy Ahmed decided to postpone the general election. As a result, both actors try to confront each other with their troops to take over the cities in Tigray. The Eritrean troops supported the Ethiopian government in human rights violations as one of their weapons that caused fear among the Ethiopian societies. The fear of being the next victim made the Ethiopian societies flee to another region in Ethiopia and become internally displaced people (IDPs). This research tries to research the role of the UNHCR in helping Ethiopian IDPs and why this refugee case needs international attention. To help the arrangement process, this research uses case-based qualitative methodology, international organization theory by Kelly Kate Pease, and human security as concepts. The result of the research found that UNHCR's role as an international organization in collaboration with other institutions and national and international organizations to assist IDPs all over the region can be classified as the role of problem-solving and aid provider.